2009
DOI: 10.1128/cvi.00409-08
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Histoplasma Antigenemia following Dissociation of Immune Complexes

Abstract: The sensitivity for detection of Histoplasma antigen is lower in serum than in urine. In other antigen assays, treatment of serum at 104°C in the presence of EDTA was required for detection of antigenemia. Sensitivity and specificity for detection of Histoplasma antigenemia were examined with or without EDTA heat treatment of the serum using the MVista Histoplasma antigen enzyme immunoassay. A total of 94.6% of serum specimens from patients with AIDS and histoplasmosis that were negative untreated were positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 7 publications
0
43
0
2
Order By: Relevance
“…More cases were tested in the current report than the previous report: 28 and 11, respectively. However, antigenemia was detected less frequently in patients with blastomycosis than in those with histoplasmosis: 90% in patients with disseminated histoplasmosis (11) and 80% in those with acute pulmonary histoplasmosis (12).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More cases were tested in the current report than the previous report: 28 and 11, respectively. However, antigenemia was detected less frequently in patients with blastomycosis than in those with histoplasmosis: 90% in patients with disseminated histoplasmosis (11) and 80% in those with acute pulmonary histoplasmosis (12).…”
Section: Discussionmentioning
confidence: 93%
“…The pretreatment procedure has been described for detection of Histoplasma antigen (11). A total of 200 l of 4% EDTA was added to 600 l of serum, vortex mixed, and placed in a heat block (Fisher Scientific) at 104°C for 6 min.…”
Section: Patientsmentioning
confidence: 99%
“…A total of 200 l of 4% EDTA at pH 4.6 was added to 600 l of sera, and the mixture was vortexed and then placed in a heat block (Fisher Scientific) at 100°C for 6 minutes, followed by centrifugation and collection of the supernatant (7).…”
Section: Methodsmentioning
confidence: 99%
“…Wheat, unpublished observations). More recently we noted that pretreatment of serum at 100°C in the presence of EDTA, by dissociating immune complexes and destroying the freed antibody, markedly improved the detection of antigenemia in histoplasmosis (7). Among AIDS patients with histoplasmosis and undetectable antigenemia, antigen was detected in 95% of samples following EDTA-heat treatment.…”
mentioning
confidence: 99%
“…One of the principal aspects that can increase the sensitivity and specificity values of PCM diagnostic tools is the treatment of the samples, such as for the elimination of immune complexes, before they are tested (22). Pretreatment has most improved the detection of antigens (antigenemia); however, some studies have also observed its importance for detecting antibodies (23).…”
mentioning
confidence: 99%